APLIKASI BRIEF PAIN INVENTORY (BPI) INDONESIAN VERSION UNTUK MENGKAJI NYERI KRONIS PADA PASIEN KANKER - Ka'arayeno, Arie Jefry (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
For cancer patients the pain will have an impact on quality of life, is complex and greatly affects daily activities. Pain management is currently felt to be not enough to relieve complaints. One major obstacle to improvement is narrow assessment, as well as an assessment focus that does not consider the multidimensional nature of pain. The Center for Symptom Evaluation in Cancer Care has developed a specific pain assessment for cancer patients, the Brief Pain Inventory (BPI). The purpose of this study is to prove and see the suitability of the Indonesian version of BPI as a study of pain in cancer patients at RSCM Jakarta. Research respondents were 20 cancer patients with pain and observed using the Brief Pain Inventory (BPI) instrument. Based on the results of the Cronbach’s alpha test from BPI it is known as 0.723. These results show that BPI is appropriate and consistent in assessing cancer pain, especially chronic pain, and has a good correlation based on the Spearman correlation with ECOG values (r = -0.75, p = 0.0001). The sensitivity test is known to be 95.7%, specificity 100 %, PPV 100%, NPV 65.67%, LR (-) 0.05, with diagnostic accuracy of 95.73%. BPI is a more multidimensional assessment as a description of biological, psychological, social and cultural conditions of cancer patients who experience pain, so that BPI is suitable for use in the scope of oncology nursing in assessing chronic pain in cancer patients.